Specific Antimicrobial Activities Revealed by Comparative Evaluation of Selected Gemmotherapy Extracts - Melinda Héjja; Emőke Mihok; Amina Alaya; Maria Jolji; Éva György; Noemi Meszaros; Violeta Turcus; Neli Kinga Oláh; Endre Máthé (MDPI AG, 2024)
Nowadays, unprecedented health challenges are urging novel solutions to address antimicrobial resistance as multidrug-resistant strains of bacteria, yeasts and moulds are emerging. Such microorganisms can cause food and feed spoilage, food poisoning and even more severe diseases, resulting in human death. In order to overcome this phenomenon, it is essential to identify novel antimicrobials that are naturally occurring, biologically effective and increasingly safe for human use. The development of gemmotherapy extracts (GTEs) using plant parts such as buds and young shoots has emerged as a novel approach to treat/prevent human conditions due to their associated antidiabetic, anti-inflammatory and/or antimicrobial properties that all require careful evaluations. Seven GTEs obtained from plant species like the olive (Olea europaea L.), almond (Prunus amygdalus L.), black mulberry (Morus nigra L.), walnut (Juglans regia L.), blackberry (Rubus fruticosus L.), blackcurrant (Ribes nigrum L.) and bilberry (Vaccinium myrtillus L.) were tested for their antimicrobial efficiency via agar diffusion and microbroth dilution methods. The antimicrobial activity was assessed for eight bacterial (Bacillus cereus, Staphylococcus aureus, Salmonella enterica subsp. enterica, Proteus vulgaris, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa and Listeria monocytogenes), five moulds (Aspergillus flavus, Aspergillus niger, Aspergillus ochraceus, Penicillium citrinum, Penicillium expansum) and one yeast strain (Saccharomyces cerevisiae). The agar diffusion method revealed the blackberry GTE as the most effective since it inhibited the growth of three bacterial, four moulds and one yeast species, having considered the total number of affected microorganism species. Next to the blackberry, the olive GTE appeared to be the second most efficient, suppressing five bacterial strains but no moulds or yeasts. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were then determined for each GTE and the microorganisms tested. Noticeably, the olive GTE appeared to feature the strongest bacteriostatic and bactericidal outcome, displaying specificity for S. aureus, E. faecalis and L. monocytogenes. The other GTEs, such as blueberry, walnut, black mulberry and almond (the list indicates relative strength), were more effective at suppressing microbial growth than inducing microbial death. However, some species specificities were also evident, while the blackcurrant GTE had no significant antimicrobial activity. Having seen the antimicrobial properties of the analysed GTEs, especially the olive and black mulberry GTEs, these could be envisioned as potential antimicrobials that might enhance antibiotic therapies efficiency, while the blackberry GTE would act as an antifungal agent. Some of the GTE mixtures analysed have shown interesting antimicrobial synergies, and all the antimicrobial effects observed argue for extending these studies to include pathological microorganisms.